PENGARUH OLEORESIN DAUN KAYU MANIS (Cinnamomum burmanii) DUA TAHAP TERHADAP KARAKTERISTIK EDIBLE FILM TAPIOKA - Rohula Utami; Lia Umi Khasanah; Katut Kompi Yuniter; Godras Jati Manuhara (Caraka Tani: Journal of Sustainable Agriculture, 2017)
Synthetic packaging caused negative impacts on environmental pollution. Utilization of edible film packaging is more effective than synthetic packaging due to the biodegradable properties. The two stages cinnamon leaves oleoresin contain active compounds that performed the antimicrobial and antioxidant activity. In this study, addition of two stages cinnamon leaves oleoresin on edible tapioca film can affect the characteristics of the edible film. Effect of two stages cinnamon leaves oleoresin on edible films characteristics was investigated. The results showed that the addition of two stages cinnamon leaves oleoresin (0%, 0.025%, 0.5%, 0.075%, and 0.1%) does not affect the thickness, tensile strength, and water vapor transmission rate of edible film, while affected the elongation and microbial inhibition of edible film. The edible film with the addition of 0.1% two stages cinnamon leaves oleoresin resulted the best microbial inhibition and physical characteristics of edible film with the thickness of 0.128 mm, tensile strength of 0.2189 MPa, elongation of 283.2721%, water vapor transmission rate of 29.786 g/jam.m2, and microbial inhibition zone of 31.394 mm.